Adolescent inpatient psychiatric admission rates and subsequent one-year mortality in England: 1998-2004. - James, A; Clacey, J; Seagroatt, V; Goldacre, M (2010)
BACKGROUND: Adolescence is a time of very rapid change not only in physical but also psychological development. During the teenage years there is a reported rise in the prevalence of psychiatric disorders. The aim of this study was to investigate age- and sex-specific National Health Service (NHS) hospital inpatient admission rates for psychiatric conditions in adolescents in England, and to examine their mortality within one year of discharge. METHOD: Using a record-linked NHS Hospital Episode Statistics (HES) dataset for England, and linked death certificates, age- and sex-specific admission rates and subsequent mortality rates were analysed by single year of age for people aged 10-19 years. RESULTS: There were similar numbers of admissions for males and females: 29,595 and 28,188 respectively. Admission rates increased substantially with increasing age, from .2 per 1000 population per year aged 10 years to 2.2 per 1000 aged 19 years. There was no appreciable difference in death rates for males and females in the year following discharge--males .23% (based on 68 deaths), females .18% (52 deaths). However, these death rates were significantly higher than those found in the general population of equivalent age: expressed as standardised mortality ratios (SMRs), setting the SMRs for males and females in the general population each as 100, the SMR in the psychiatric population were 518 (95% CI 402-657) for males and 937 (692-1225) for females. The diagnostic groups with the highest mortality were development disorders (SMR 3017, 95% CI 1757-4831), eating disorders (SMR 1103, 443-2272), and affective disorders (SMR 940, 589-1423). CONCLUSION: Adolescent psychiatric disorders represent a serious public health issue, with a steep rise in hospital admissions during the teenage years, and a six-fold increased death rate within one year of discharge compared to the general population of the same age.